Recovery, responsiveness and interpretability of patient-reported outcome measures after surgery for Dupuytren’s disease - Rodrigues, J.N.; Zhang, W.; Scammell, Brigitte E.; Davidson, D.; Fullilove, S.; Chakrabarti, I.; Russell, P.G.; Davies, T.R.C. (SAGE, 2016)
This prospective cohort study investigated the responsiveness and interpretability of the Disabilities of the Arm, Shoulder and Hand (DASH) and Unité Rhumatologique des Affections de la Main (URAM) outcome measures for assessing recovery after fasciectomy and dermofasciectomy for Dupuytren’s disease. DASH outcome scores at 1 year were significantly better than at 6 weeks, suggesting that recovery is not complete by 6 weeks. Of the 101 patients recruited to the DASH cohort, 71 completed preoperative, 6 week and 1 year postoperative DASH scores; 68 of them completed preoperative and 1 year postoperative DASH scores and an external anchor question. In the URAM cohort, 30/44 completed the preoperative and the 1 year postoperative URAM scores and the anchor question. The DASH score exhibited moderate responsiveness but poor interpretability on receiver operating characteristic curve analysis, such that a minimal important change could not be estimated. The URAM score showed acceptable responsiveness, and an MIC of 10.5 on receiver operating characteristic analysis.